EXPERIMENTAL STUDY TO DETERMINE THE LOCAL CONDENSATION HEAT TRANSFER COEFFICIENTE FOR R134A FLOWING THROUGH A 4.8 MM INTERNAL DIAMETER SMOOTH HORIZONTAL TUBE - Mendes, R. P.; Pottie, D. L.; Paula, C. H.; Pabon, J. G.; Machado, L. (Revista de Engenharia Térmica, 2021)
Refrigerant fluid R134a is commonly one of the most utilised in vapour compression cycles wordlide, wheter in dommestic HVAC or automotive regrigeration systems. This paper’s goal is to experimetnally determine the fluid local condensation Heat Transfer Coefficient (HTC), in several flor regimes. In this work, the mass flux was equal to 200, 250 and 300 kg/(m2s) and the fluid flowed through a smooth, horizontal 4.8 mm internal diameter aluminium pipe, during which its vapour quality varied along the entire quality range. A purpose built test rig was developed, in which fluid conditions were constantly monitored and controlled. Through measurements in temperature and pressure, an energy balance was used to calculate experimentally the local heat transfer coeeficient. Average results for the unit quality range equalled to 3781 , 3459 and 3944 W/m2K for saturation temperature equal to 30 C and the aforementioned mass velocities. Likewise, at 35C the averages HTC found were 2903, 3141 and 3898 W/m2K at the same mass flux rates. Later on, the experimental results were compared to ten commonly used HTC correlation found in relevant references, with Chato’s correlation returning the best fitting.